Dielectric characterization of water glucose solutions using a transmission/reflection line method. (January 2017) - Juan, Carlos G.; Bronchalo, Enrique; Torregrosa, Germán; Ávila, Ernesto; García, Nicolás; Sabater-Navarro, José M.
Highlights: We present a dielectric permittivity measuring method based on a transmission/reflection line. The method is tested and its proper performance is assessed. Water glucose solutions at several concentrations are measured and their dielectric permittivities are obtained. Discussion of the results is presented and conclusions regarding the future development of a non-invasive blood glucose meter based on dielectric means are offered. Abstract: Diabetes mellitus (DM) is a disease that affects millions of people worldwide. In order to be managed, it requires the individuals to measure their blood glucose level in an uncomfortable way several times every day. Thereby, a reliable non-invasive, non-painful blood glucose monitoring system is desirable. Microwave technology has been regarded previously to develop such a sensor by dielectric means, but no clear dielectric characterization of blood glucose dielectric behavior has been hitherto shown. In this paper, a novel study of the effect on the dielectric behavior of water when glucose is added is presented, as a simplified case of blood glucose dielectric behavior. Different water glucose solutions have been dielectrically characterized using a transmission/reflection line method and the effect of the changes of the glucose level in the dielectric behavior has been discussed. Conclusions concerning the development of a non-invasive blood glucose sensor are offered and their validity is discussed.